Preliminary Studies in Soybean (Glycine Mai (L) Merrill) Productivity on the Accra Plains - Boakye-Boaten, K.B. (University of Ghana, 1974)
Experiments on mulching, temperature, storage end inter-row spacing were conducted in the fie ld and laboratory during the major and minor seasons o f 1973* with 21 introduced soybean varieties including H ill, Kent, CBS 486 and Aasoy 71. 1. Mulching Kxperiments Three varieties (H ill, Kent, GES 466) were grown in two fie ld trials and a pot experiment with and without mulch applied after planting in 1973* Mulching decreased maximum s o il temperature; maintained higher s o il moisture content* improved seedling emergence! increased plant height, seed si?.e and grain yield in the major season. In the minor season, mulching increased nodes and pods per plant, seed size and lodging. GrsLn yield was not increased most likely due to the increased lodging and pest infestation. In the pot experiment, mulching hastened flowering; increased stem diameter, plant height, flowers, nodes and pods per plants the percentage of flowers which formed pods and seed yield. Mulching appeared beneficial particularly when seed v iab ility was low and soil temperatures were high. 2. Temperature Experiments Twenty-one varieties were sown in trays and kept in incubators at 20, 30, 40 and 50°C. termination and emergence were high but slow at 20°C. There was no germination at 5Q°C. .Doubling the temperature from 20 to 40°C reduced days to f i r s t emergence and days to maximum emergence by 50/., however, maximum number o f seedlings that emerged as well as hypocotyl elongation were reduced by approximately 4($, and 30^ respectively. Hypocotyl elongation was better at 30°C than at 20 or 40°C by 20, end 30$ respectively. Based on their ability to consistently germinate and emerge well at the higher temperature (40 C), the varieties Cutler 71≫ Semmes, Hark and Dare were found to perform well, while Hutton, H ill, Clark 63 and Jupiter were the poorest* 3. Storage Experiments Soybean (cv. Anisoy 71) seed of in it ia l moisture content 11.2$ was stored in cloth or polythene bags at ambient temperature and relative humidity (27°C, 76/> HH)≫ in an air-conditioned room (22°C, 592R &H) and in a walk-in cold room (2°C, BE). Seed at 14≪5 and 17 »Q/o moisture also was stored in the air-conditioned room. Seed samples stored at high temperature end moisture contents rapidly lost their a b ility to germinate and emerge after 9-10 weeks. Lowering temperatures or moisture content preserved seed v iab ility longer. Seed in polythene Dag at 22 or 2o C and 11.2/e moisture did not lose v ia b ility during 50 and 55 weeks respectively of storage. 4. Inter-row Spacing la:periments Two varieties (H ill; CIS 486) were sown in the fie ld in rows 25, 50 and 75cm apart during the major and minor seasons of 1973* The number o f main-stern bronchos and pods per plant significantly increased -with increasing row spacing. 'Chs ta l l variety, CES 486, lodged more than the snort variety, H ill. Seed size was not significantly affeotefi, however, seed yield tended to be higher in rows 25cm apart for the short determinate variety (H i ll)f and in rows 75c® apart, for the ta ll indeterminate variety CSS 486, the latter outyielding Hill, which matured earlier. 5. It was concluded from the results of these studies that soybean production on the Southern part of Ghana, at least on small holdings, would be possible.
Thesis(MSc)-University of Ghana, 1974
Keywords: Preliminary Studies; Soybean (Glycine Mai (L) Merrill); Accra Plains